2007
DOI: 10.1089/ten.2006.0431
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Mouse Articular and Growth Plate Cartilage

Abstract: Articular cartilage is recalcitrant to repair and regeneration. Tissue engineering and regenerative medicine are potential strategies to treat the damage to articular cartilage. A thorough understanding of the gene expression profiles in articular cartilage and growth plate chondrocytes will be an important prerequisite for tissue engineering of cartilage. Regeneration is a recapitulation of embryonic development and morphogenesis. We used laser capture microdissection to capture the surface articular chondroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
37
0
5

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 29 publications
4
37
0
5
Order By: Relevance
“…Expression profile studies have shown that articular chondrocytes express EPCR (in the mouse [28]) and TM (in the rat [29]), with TM also being increased in surgically induced OA in the rat. The results of the present study extend these previous observations to show the expression of protein C, EPCR, and TM in both human and ovine articular chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Expression profile studies have shown that articular chondrocytes express EPCR (in the mouse [28]) and TM (in the rat [29]), with TM also being increased in surgically induced OA in the rat. The results of the present study extend these previous observations to show the expression of protein C, EPCR, and TM in both human and ovine articular chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…B то же время содержание аггрекана в этой зоне ниже, чем в дру-гих. Она богата регуляторными молекулами, такими как ТФР β1 и 3, и белками морфогенеза кости (БМК) 1-6 [41,42]. Пролиферативный потенциал клеток этого слоя опре-деляется экспрессией циклина D2.…”
unclassified
“…Пролиферативный потенциал клеток этого слоя опре-деляется экспрессией циклина D2. Однако деление может ингибироваться специфическими генами Gas1 и GADD45α, которые здесь также обнаружены [42]. Это мо-жет служить объяснением сложности выявления пролифе-ративной активности путем окрашивания на PCNA (ядер-ный антиген пролиферирующих клеток) [43].…”
unclassified
See 2 more Smart Citations